Penerapan Prinsip Pengelolaan Dana Desa Di Desa Tahunan Kabupaten Jepara - Ika Nurmayanti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
There are still many villages that have not implemented these principle so that they are subject to legal cases. This study aims to see the extent to which the Tahunan Village applies the principles of transparency, accountability and participation in the process of managing village funds. The research method used is descriptive with a qualitative approach. Data collection techniques are observation, interviews and literature study. The results show that the Tahunan Village has implemented village fund management in accordance with the principles of transparency, accountability and participatory. All stakeholders involved play an active role in managing village funds, although one stakeholder, farmer group association, remains passive. There are obstacles in the process of managing village funds, including the lack of capacity of village officials and lack of the understanding of the community about the process of managing village funds.